Response of a large deep-seated gravitational slope deformation to meteorological, seismic, and deglaciation drivers as measured by InSAR - Rabus, Bernhard; Engelbrecht, Jeanine; Clague, John J.; Donati, Davide; Stead, Doug; Francioni, Mirko (Frontiers in Earth Science, 2022)
We analyze the sensitivity of a large (area extent ∼3 km2), deep-seated gravitational slope deformation (Fels slide, Alaska Range) to three specific drivers: (i) liquid surface water input from ERA-5 reanalysis snow melt and rainfall; (ii) locally projected seismic activity of Alaskan earthquakes; and (iii) lowering of Fels Glacier at the slide toe estimated from topographic data. A surface displacement map-series is derived from 1991 to 2016 spaceborne multi-sensor InSAR data (ERS, RADARSAT-1/2, ALOS, TerraSAR-X) using adaptive demodulation to unwrap interferograms of variable spatial resolution and quality. On this series we use independent component analysis (ICA) to uncover five displacement patterns that map to independently moving domains of the slide and then correlate the corresponding temporal pattern intensities with the suspected drivers. We find significant sub-annual correlation between displacement pattern intensities and seasonal water input variations. The correlation can be optimized, for each ICA pattern, by choosing appropriate values of temporal smoothing and lag to create depth-propagated versions of the water input driver. Lag time results ranging from one to 3 weeks relate to shallower and deeper propagations of water input, driving the different deformation patterns. For two of the deformation patterns, seasonal sensitivity to water input was strongly amplified by the 2002 Mw7.9 Denali earthquake. Sensitivity of these patterns remained high for 4 years until abruptly dropping to below pre-earthquake values, which suggests a highly non-linear modulation by the seismic driver. Other deformation patterns show a steady intensity increase that appears linked to the deglaciation driver. Despite these observations, the inter-annual variations in ICA pattern intensities show no clear predictability by individual drivers or driver combinations. This suggests that the mechanical and hydraulic evolution of the slide, especially after damaging events such as earthquakes or heavy rainfall, is a crucial factor not adequately modeled in our approach. Despite this limitation, our analysis provides the first direct evidence that the Fels slide comprises several independently moving domains that respond differently to the suspected drivers as is suggestive of a complex slope deformation.